Environmental sustainability of food production and consumption in the Nordic and Baltic region – a scoping review for Nordic Nutrition Recommendations 2023 - Helen Harwatt; Tim G. Benton; Jan Bengtsson; Bryndís Eva Birgisdóttir; Kerry Ann Brown; Corné van Dooren; Maijaliisa Erkkola; Morten Graversgaard; Thorhallur Halldorsson; Michael Hauschild; Anne Høyer-Lund; Jelena Meinilä; et al. (Food & Nutrition Research)
This scoping review examines environmental impacts related to food production and consumption in Nordic and Baltic countries. The overarching advice to all Nordic and Baltic countries, in line with the current body of scientific literature, is to shift to a more plant-based dietary pattern and avoid food waste. Taking into account current consumption patterns, there is a high potential and necessity to shift food consumption across the countries to minimise its environmental impact. More specifically, a substantial reduction in meat and dairy consumption and increased consumption of legumes/pulses, whole grains, vegetables, fruits, nuts, and seeds are suggested as a priority intervention. Reducing the environmental impacts of seafoods is also key and suggestions include a shift to seafoods with lower environmental impacts such as seaweed and bivalves. As part of the suggested transition to a more plant-based diet, the scope for increasing the provision of plant-based foods through increasing the cultivation of legumes/pulses, vegetables, and grains and through feed-to-food shifts within the region should be explored.